Synthesis, Structure, and Magnetic Properties of a Family of Complexes Containing a CoII2DyIII Pivalate Core and a Pentanuclear CoII4DyIII Derivative. Issue 12 (21st December 2017) - Kiskin, Mikhail; Zorina‐Tikhonova, Ekaterina; Kolotilov, Sergey; Goloveshkin, Alexander; Romanenko, Galina; Efimov, Nikolay; Eremenko, Igor
Abstract : A series of new Co II –Ln III complexes with polynuclear Co2 Ln(NO3 )(Piv)6 (Ln = La, Gd, Dy; Piv = pivalate) cores were prepared by self‐assembly reactions or step‐by‐step assembly. [Co2 Dy(NO3 )(Piv)6 (MeCN)2 ] was used as the starting compound for the synthesis of the trinuclear analogue [Co2 Dy(NO3 )(Piv)6 (py)2 ] (py = pyridine) and the pentanuclear complex [Co2 Dy(NO3 )(Piv)6 CoL(Piv)(H2 O)2 ][NO3 ]2 [L = 2, 6‐bis(2‐pyridyl)‐4‐(4‐pyridyl)pyridine]. The effects of the coordination environment and temperature on the distortion of the Ln III coordination polyhedra were analyzed for a series of coordination compounds with M II 2 Ln III cores and close analogues. The distortion of the Ln III polyhedron depends on both the composition of the compound and the temperature; a temperature increase favors the D 2 d geometry of the Ln III coordination polyhedron. The magnetic properties of the complexes with Co II 2 Dy III cores were analyzed with consideration of the anisotropy of the Co II and Dy III ions. The compounds containing diamagnetic La III and isotropic Gd III ions, [Co2 Ln(Piv)6 (NO3 )(MeCN)2 ] (Ln = La, Gd), which are isostructural to the Co II Dy III analogue, were studied to evaluate the Co II magnetic‐anisotropy parameters to minimize the overparameterization of the magnetic properties in the fits for the Co2 Dy systems. The magnetic properties of all complexes in this study are governed mainly by the magnetic properties of the isolated ions. Abstract : A series of complexes with a trinuclear Co II 2 Dy III core along with a pentanuclear Co II –Co II 2 Dy III –Co II derivative are prepared by self‐assembly or step‐by‐step assembly reactions. The effects of the coordination environment and temperature on the distortion of the Ln III polyhedron are analyzed. The magnetic data are simulated with consideration of the anisotropy of the Co II and Dy III ions.